Niobium and aluminum co-modified positive electrode material as well as construction method and application thereof

By constructing a composite interface layer co-modified by niobium and aluminum on the surface of the positive electrode material of lithium-ion batteries, the problems of structural instability and capacity attenuation of high-nickel ternary positive electrode material under high cut-off voltage are solved, and a positive electrode material with high stability and excellent electrochemical performance is achieved, with a simple process and low cost.

CN119725412AActive Publication Date: 2025-03-28INST OF CHEM CHINESE ACAD OF SCI

Patent Information

Application Number
CN202311263381.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-27
Publication Date
2025-03-28
Estimated Expiration
2043-09-27

AI Technical Summary

Technical Problem

The existing high-nickel ternary cathode materials have problems of structural instability and rapid capacity attenuation at high cutoff voltages, and the existing coating methods are difficult to achieve uniform distribution and precise control.

Method used

By constructing a composite interface layer of niobium and aluminum co-modified on the surface of the positive electrode material, a mixture of soluble metal niobium salt, aluminum salt and alcohol solvent is used to form solution A, and mixed with suspension B of the positive electrode active material, and after stirring and calcining, a surface structure with high stability is formed.

Benefits of technology

The high stability and excellent electrochemical properties of the cathode material are achieved, especially the cycle stability under high voltage conditions is significantly improved, and the process is simple and cost-effective, and it is suitable for large-scale processing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119725412A_ABST
    Figure CN119725412A_ABST
Patent Text Reader

Abstract

The invention discloses a niobium and aluminum co-modified positive electrode material and a construction method and application thereof. The construction method comprises the following steps: (1) mixing soluble metal niobium salt, metal aluminum salt and an alcohol solvent, and reacting to form a solution A; (2) adding a positive active material into an anti-solvent, and mixing to form a turbid liquid B; (3) mixing the solution A obtained in the step (1) with the turbid liquid B obtained in the step (2), and reacting under stirring to obtain powder with uniformly coated surface; and (4) calcining the powder with the uniformly coated surface obtained in the step (3) to obtain the niobium and aluminum co-modified positive electrode material. An Nb and Al co-modified interface is constructed on the surface of the positive electrode material, so that the performance of the positive electrode material in an extreme environment such as high voltage is remarkably improved, and the positive electrode material has excellent high-voltage stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of energy materials, and relates to a niobium and aluminum co-modified positive electrode material, a construction method and application thereof, and specifically relates to a method for regulating the interface of a positive electrode material, and specifically relates to controllably constructing a niobium and aluminum co-modified composite interface layer on the surface of a positive electrode material to prepare a lithium ion battery positive electrode material with a highly stable surface structure and excellent electrochemical properties. Background Art

[0002] The rapid increase in energy density of lithium-ion batteries (LIBs) has led to their rapid application in electric vehicles and portable electronic devices. The positive electrode material is a key factor in determining the energy density of lithium-ion batteries. Among the many materials, high-nickel ternary positive electrode materials LiNi x Co y Mn 1-x-y O2 (x ≥ 0.8) has high energy density and power density and is considered to be one of the most ideal cathode materials for next-generation lithium-ion batteries. Among them, the capacity of ternary cathode materials mainly depends on the content of Ni. A high Ni content will lead to a higher specific capacity, but also make the material have a worse cycle stability. Especially at high cut-off voltages, on the one hand, the cathode material in a deep delithiation state has a higher content of highly oxidized Ni. 4+ , which will cause serious irreversible side reactions between the material surface and the electrolyte, greatly reduce the structural stability of the positive electrode material, increase the interfacial impedance, and thus lead to rapid capacity decay; on the other hand, the battery will be accompanied by irreversible structural phase changes and anisotropic volume changes during repeated charging and discharging, which will lead to the risk of structural degradation such as particle cracks or even breakage of the positive electrode material.

[0003] Therefore, it is particularly important to modify the interface of high-nickel ternary positive electrode materials. Surface coating is regarded as an effective modification strategy. By constructing a uniform and thin buffer layer on the surface of the positive electrode material, the contact reaction between the positive electrode active material and the organic electrolyte can be effectively blocked, which can play a good role in stabilizing the interface structure. At the same time, lithium ions are allowed to be transmitted between the electrolyte and the positive electrode material without causing a large loss of electrode capacity. However, current coating methods such as the solid-phase mixed sintering used in the invention patent CN109950498A and the liquid-phase evaporation solvent used in the patent CN108336348A are difficult to achieve uniform distribution of coated species on the surface of the positive electrode material, and it is even more difficult to achieve precise control of the true state of the electrode material surface, resulting in the ultimate inability to systematically study the corresponding relationship between the coating and the structure and performance. In order to achieve this goal, it is extremely important to construct a uniform and controllable interface protection layer to regulate the surface state of the positive electrode material, so as to maximize the structural stability and cycle stability of the high-nickel ternary positive electrode material. Although atomic layer deposition technology can achieve uniform deposition of a single species on the positive electrode material, it is extremely challenging to uniformly and controllably construct multiple composite species. At the same time, this method is cumbersome to operate and extremely costly, so it is difficult to achieve large-scale production applications.

[0004] Therefore, based on the above factors, inventing a protection strategy that is low-cost, can be processed in large quantities, and can achieve uniform and controllable surface regulation of positive electrode materials is of great significance to the development of positive electrode materials for lithium-ion batteries. Summary of the invention

[0005] The purpose of the present invention is to construct a method and application of a niobium and aluminum co-modified positive electrode material, and to stabilize the interface structure of the positive electrode material by introducing a composite strategy, thereby improving the cycle life and rate performance of the battery.

[0006] In order to achieve the above technical objectives, the present invention adopts the following technical solutions:

[0007] A method for constructing a positive electrode material co-modified with niobium and aluminum, the method comprising the following steps:

[0008] (1) mixing a soluble metal niobium salt, a metal aluminum salt and an alcohol solvent and reacting them to form a solution A;

[0009] (2) adding the positive electrode active material to the anti-solvent and mixing to form a suspension B;

[0010] (3) mixing the solution A obtained in step (1) with the suspension B obtained in step (2), and reacting them under stirring to obtain a powder with a uniform surface coating;

[0011] (4) calcining the powder with uniform surface coating obtained in step (3) to obtain a positive electrode material co-modified with niobium and aluminum.

[0012] According to an embodiment of the present invention, in step (1), the alcohol solvent includes but is not limited to one or more of ethylene glycol, propylene glycol, tetraethylene glycol, diethylene glycol, triethylene glycol, tetraethylene glycol, hexaethylene glycol, octaethylene glycol, polyethylene glycol 200, polyethylene glycol 400, and polyethylene glycol 600, preferably diethylene glycol.

[0013] According to an embodiment of the present invention, in step (1), the soluble niobium salt is selected from at least one of soluble metal niobium salts containing metal niobium element, such as niobium chloride, niobium nitrate, niobium ethoxide, niobium oxalate, etc., and more preferably niobium ethoxide.

[0014] According to an embodiment of the present invention, in step (1), the soluble aluminum salt is selected from at least one of the soluble metal aluminum salts containing metallic aluminum element, such as aluminum chloride, aluminum nitrate, aluminum sulfate, aluminum ethanol, aluminum oxalate, etc., and more preferably aluminum nitrate.

[0015] According to an embodiment of the present invention, in step (1), the concentration of the soluble niobium salt in solution A is 1×10 -4 ~1mol / L, more preferably 1×10 -3 ~0.5mol / L.

[0016] According to an embodiment of the present invention, in step (1), the concentration of the soluble aluminum salt in solution A is 1×10 -4 ~1mol / L, more preferably 1×10 -3 ~0.5mol / L.

[0017] According to an embodiment of the present invention, in step (1), the reaction conditions for forming solution A include: the reaction temperature is room temperature to 50°C, preferably room temperature; the reaction time is 2h-72h, preferably 12h.

[0018] According to an embodiment of the present invention, in step (2), the positive electrode active material includes but is not limited to at least one of the positive electrode materials of lithium ion batteries, such as high nickel ternary nickel cobalt manganese oxide, lithium nickel oxide, lithium cobalt oxide, lithium manganese oxide, lithium-rich manganese-based materials, lithium nickel manganese oxide, lithium nickel cobalt oxide, lithium nickel cobalt aluminum oxide, lithium titanate, lithium iron phosphate, sodium ion battery positive electrode materials, and potassium ion battery positive electrode materials; for example, selected from high nickel ternary nickel cobalt manganese oxide materials.

[0019] According to an embodiment of the present invention, in step (2), the concentration of the positive electrode active material is 1×10 -2 ~20 mol / L, more preferably 1~15 mol / L.

[0020] According to an embodiment of the present invention, in step (2), the anti-solvent includes but is not limited to at least one of methanol, ethanol, propanol, acetone, butanone, chloroform, dichloromethane, furfural, acetonitrile, dioxane, ethyl acetate, acetic acid, formic acid, acetic anhydride, acetylacetone, acetaldehyde, and tetrahydrofuran, preferably acetone.

[0021] According to an embodiment of the present invention, in step (2), the mixing is performed under stirring.

[0022] According to an embodiment of the present invention, in step (3), the method of mixing solution A with suspension B comprises: directly pouring the solution, slowly dripping, and controlling the dripping rate by a peristaltic pump to drip into solution B; or, directly pouring solution B, slowly dripping, and controlling the dripping rate by a peristaltic pump to drip into solution A, preferably, slowly dripping solution A into suspension B by a peristaltic pump. Preferably, the dripping rate controlled by the peristaltic pump is 0.1 ml / min-30 ml / min.

[0023] According to an embodiment of the present invention, in step (3), the stirring temperature is room temperature to 50° C., preferably room temperature.

[0024] According to an embodiment of the present invention, in step (3), the stirring speed is between 100 r / min and 1000 r / min, preferably 600 r / min.

[0025] According to an embodiment of the present invention, in step (3), the coating layer thickness of the powder uniformly coated on the surface is between 1 and 200 nm.

[0026] According to an embodiment of the present invention, in step (4), the calcination atmosphere is at least one of oxygen, air, nitrogen, and argon, preferably oxygen;

[0027] According to an embodiment of the present invention, in step (4), the calcination temperature is 200 to 900° C., preferably 500 to 800° C.;

[0028] According to an embodiment of the present invention, in step (4), the calcination time is 1 to 10 hours, preferably 1 to 5 hours.

[0029] According to an embodiment of the present invention, in step (4), the shell structure of the positive electrode material co-modified with Nb and Al is a composite interface layer containing niobium and aluminum.

[0030] The present invention also provides a positive electrode material co-modified with Nb and Al, and the positive electrode material is obtained by the above-mentioned construction method.

[0031] According to an embodiment of the present invention, the Nb and Al co-modified positive electrode material is a particle having a core-shell structure.

[0032] According to an embodiment of the present invention, the Nb and Al co-modified positive electrode material includes a shell structure and a positive electrode active substance, wherein the shell structure is modified on the surface of the positive electrode active substance; the positive electrode active substance has the meaning as described above; and the shell structure includes at least Nb and Al elements.

[0033] Preferably, the shell structure partially or completely covers the surface of the positive electrode active material, preferably completely covers it. Further, the shell structure is continuously and evenly distributed on the surface of the positive electrode active material.

[0034] According to an embodiment of the present invention, the thickness of the shell structure is 0 nm to 200 nm, for example, 1 nm, 1.5 nm, 5 nm, 10 nm, 50 nm, 100 nm, or 150 nm.

[0035] The present invention also provides the use of the above-mentioned Nb and Al co-modified positive electrode material in energy storage batteries, such as high-voltage lithium-ion batteries.

[0036] Beneficial effects:

[0037] The present invention provides a method for constructing a positive electrode material co-modified with Nb and Al, the method having the advantages of simple process flow, low cost, and suitability for large-scale processing of large quantities of samples, and the non-aqueous solvent environment can ensure non-destructive modification of the positive electrode material. The method introduces different metal elements conveniently and simultaneously through the interaction between the precursor solvent, the metal salt, and the anti-solvent, so that the coating species containing Nb and Al are slowly deposited on the surface of the positive electrode particles to form a uniform and continuous coating layer. Through a further high-temperature calcination process, a positive electrode material with double surface modification of Nb and Al can be obtained. By regulating the ratio of Nb / Al, the thickness of the coating layer, the calcination temperature, and the calcination time, the state of the positive electrode surface can be effectively controlled, thereby achieving excellent comprehensive electrochemical performance.

[0038] The present invention constructs a Nb and Al co-modified interface on the surface of the positive electrode material, and the elements Nb and Al simultaneously undergo an interfacial reaction on the surface of the positive electrode material, thereby creating a unique and more stable surface structure driven by high-temperature heat treatment, ultimately achieving a significant improvement in the performance of the positive electrode material under extreme environments such as high voltage, and having excellent high-voltage stability.

[0039] The present invention can carry out large-scale coating treatment on positive electrode materials under anhydrous and mild conditions, introduce a coating layer containing niobium and aluminum at the interface of the positive electrode material at the same time, and strengthen the interaction between different coating elements and the layered positive electrode through calcination treatment, thereby playing a dual role of systematically regulating the interface stability and cycle stability of the positive electrode material from a structural perspective. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] Figure 1 This is a scanning electron microscope (SEM) image of the high nickel single crystal positive electrode material co-modified with Nb and Al interfaces in Example 1.

[0041] Figure 2 This is the X-ray diffraction (XRD) pattern of the high nickel single crystal positive electrode material co-modified with Nb and Al interfaces in Example 1.

[0042] Figure 3 This is a transmission electron microscope (TEM) image of the high nickel single crystal positive electrode material co-modified with Nb and Al interfaces before calcination in Example 1.

[0043] Figure 4 This is a transmission electron microscope (TEM) image of the high nickel single crystal positive electrode material co-modified with Nb and Al interfaces before calcination in Example 1 at high magnification.

[0044] Figure 5 The charge and discharge curves of the high nickel single crystal positive electrode materials in Example 1 and Comparative Example 1 at a 0.2C rate (4.3V).

[0045] Figure 6 It is a cycle performance diagram of the high nickel single crystal positive electrode material in Example 1 and Comparative Example 1 at 1C rate (4.3V).

[0046] Figure 7 This is a cycle performance diagram of the high nickel single crystal positive electrode material in Example 1 and Comparative Example 1, Comparative Example 2, and Comparative Example 3 at 1C rate (4.5V). DETAILED DESCRIPTION

[0047] The technical scheme of the present invention will be further described in detail below in conjunction with specific embodiments. It should be understood that the following embodiments are only exemplary descriptions and explanations of the present invention and should not be construed as limiting the scope of protection of the present invention. All technologies implemented based on the above content of the present invention are included in the scope that the present invention is intended to protect.

[0048] Unless otherwise specified, the raw materials and reagents used in the following examples are commercially available or can be prepared by known methods.

[0049] Example 1

[0050] (I) Modification of positive electrode materials

[0051] 1) Dissolve 0.16 ml of niobium ethoxide and 0.19 g of aluminum nitrate nonahydrate in 10 ml of diethylene glycol, and stir at room temperature for 12 hours to form a precursor solution A;

[0052] 2) 10g high nickel single crystal positive electrode LiNi 0.8 Co 0.1Mn 0.1 O2(NCM) particles (particle size 1-10 μm) were dispersed in 40 ml of acetone and dispersed evenly by ultrasonic stirring to form suspension B;

[0053] 3) The precursor solution A is slowly added dropwise to the suspension B by a peristaltic pump at a dropping speed of 0.1 ml / min-30 ml / min, and stirring is continued at room temperature for 1 hour. After centrifugation, washing, and drying, a powder with a uniform surface coating is obtained;

[0054] 4) The powder with uniform surface coating obtained in step 3) is calcined at 750° C. in an oxygen atmosphere for 2 h to form a high nickel single crystal positive electrode material with dual modification of Nb and Al.

[0055] (II) Structural and morphological characterization

[0056] The surface morphology of the modified samples was observed using a scanning electron microscope (SEM-8100). Figure 1 The results show that the cathode material after interface modification maintains the basic single crystal morphology of the cathode material, and there is no enrichment of modified species on the surface. The crystal structure of the modified NCM single crystal was analyzed using a powder X-ray diffractometer (D8 Advance, Brune). The results are as follows: Figure 2 As shown in the figure, the modified cathode material maintains the typical layered structure of NCM ternary cathode without other impurity peaks, indicating that the interface modification does not destroy the crystal structure of NCM. The surface state of the coated particles was observed using a transmission electron microscope (TEM-2100F). Figure 3 The results show that a uniform and continuous coating layer is formed on the surface of the positive electrode particles. Figure 4 It was further learned that its thickness was about 5 nm.

[0057] (III) Preparation of interface-modified NCM electrode sheets

[0058] 0.24 g of the Nb and Al dual-modified high-nickel single crystal positive electrode particles prepared above was mixed with 0.03 g of the conductive additive Super-P, 0.6 g of 5% mass concentration of PVDF as a binder, and a small amount of solvent NMP. After slurrying, coating (aluminum sheet as current collector), and drying, an interface-modified NCM electrode sheet was obtained.

[0059] (IV) Battery Assembly

[0060] The above-mentioned interface-modified NCM electrode sheet was used as the positive electrode, lithium metal was used as the negative electrode, a polypropylene microporous membrane (Celgard 2400) was used as the separator, and 1.15 mol / L LiPF6 was used as the electrolyte to assemble a button cell in an argon-protected glove box.

[0061] (V) Battery test

[0062] The battery was subjected to constant current charge and discharge test using a Blue Electric charge and discharge instrument, cycled at 1C rate (1C = 200 mA / g), of which the first three cycles were 0.2C activation stage, and the test temperature was 25° C. The battery specific capacity and charge and discharge current were calculated based on the mass of NCM.

[0063] Example 2

[0064] (I) Modification of positive electrode materials

[0065] 1) Dissolve 0.16 ml of niobium ethoxide and 0.38 g of aluminum nitrate nonahydrate in 10 ml of diethylene glycol, and stir at room temperature for 12 hours to form a precursor solution A;

[0066] 2) 10g high nickel single crystal positive electrode LiNi 0.8 Co 0.1 Mn 0.1 O2(NCM) particles (particle size 1-10 μm) were dispersed in 40 ml of acetone and dispersed evenly by ultrasonic stirring to form suspension B;

[0067] 3) The precursor solution A is slowly added dropwise to the suspension B by a peristaltic pump, and the mixture is stirred for 1 hour at room temperature. A powder with a uniform surface coating is obtained by centrifugation, washing, and drying.

[0068] 4) The powder with uniform surface coating obtained in step 3) is calcined at 750° C. in an oxygen atmosphere for 2 h to form a high nickel single crystal positive electrode material with dual modification of Nb and Al.

[0069] (ii) Structural and morphological characterization (specific steps are the same as in Example 1).

[0070] (III) Preparation of interface-modified NCM electrode sheet (specific steps are the same as those in Example 1).

[0071] (IV) Assembling the battery (the specific steps are the same as those in Example 1).

[0072] (V) Battery testing (specific steps are the same as in Example 1).

[0073] Example 3

[0074] (I) Modification of positive electrode materials

[0075] 1) Dissolve 0.16 ml of niobium ethoxide and 0.095 g of aluminum nitrate nonahydrate in 10 ml of diethylene glycol, and stir at room temperature for 12 hours to form a precursor solution A;

[0076] 2) 10g high nickel single crystal positive electrode LiNi 0.8 Co 0.1 Mn 0.1O2(NCM) particles (particle size 1-10 μm) were dispersed in 40 ml of acetone and dispersed evenly by ultrasonic stirring to form suspension B;

[0077] 3) The precursor solution A is slowly added dropwise to the suspension B by a peristaltic pump, and the mixture is stirred for 1 hour at room temperature. A powder with a uniform surface coating is obtained by centrifugation, washing, and drying.

[0078] 4) The powder with uniform surface coating obtained in step 3) is calcined at 750° C. in an oxygen atmosphere for 2 h to form a high nickel single crystal positive electrode material with dual modification of Nb and Al.

[0079] (ii) Structural and morphological characterization (specific steps are the same as in Example 1).

[0080] (III) Preparation of interface-modified NCM electrode sheet (specific steps are the same as those in Example 1).

[0081] (IV) Assembling the battery (the specific steps are the same as those in Example 1).

[0082] (V) Battery testing (specific steps are the same as in Example 1).

[0083] Example 4

[0084] (I) Modification of positive electrode materials

[0085] 1) Dissolve 0.16 ml of niobium ethoxide and 0.19 g of aluminum nitrate nonahydrate in 10 ml of diethylene glycol, and stir at room temperature for 12 hours to form a precursor solution A;

[0086] 2) 10g high nickel single crystal positive electrode LiNi 0.8 Co 0.1 Mn 0.1 O2(NCM) particles (particle size 1-10 μm) were dispersed in 40 ml of acetone and dispersed evenly by ultrasonic stirring to form suspension B;

[0087] 3) The precursor solution A is slowly added dropwise to the suspension B by a peristaltic pump, and the mixture is stirred for 1 hour at room temperature. A powder with a uniform surface coating is obtained by centrifugation, washing, and drying.

[0088] 4) The powder with uniform surface coating obtained in step 3) is calcined at 700° C. in an oxygen atmosphere for 2 h to form a high nickel single crystal positive electrode material with dual modification of Nb and Al.

[0089] (ii) Structural and morphological characterization (specific steps are the same as in Example 1).

[0090] (III) Preparation of interface-modified NCM electrode sheet (specific steps are the same as those in Example 1).

[0091] (IV) Assembling the battery (the specific steps are the same as those in Example 1).

[0092] (V) Battery testing (specific steps are the same as in Example 1).

[0093] Example 5

[0094] (I) Modification of positive electrode materials

[0095] 1) Dissolve 0.16 ml of niobium ethoxide and 0.19 g of aluminum nitrate nonahydrate in 10 ml of diethylene glycol, and stir at room temperature for 12 hours to form a precursor solution A;

[0096] 2) 10g high nickel single crystal positive electrode LiNi 0.8 Co 0.1 Mn 0.1 O2(NCM) particles (particle size 1-10 μm) were dispersed in 40 ml of acetone and dispersed evenly by ultrasonic stirring to form suspension B;

[0097] 3) The precursor solution A is slowly added dropwise to the suspension B by a peristaltic pump, and the mixture is stirred for 1 hour at room temperature. A powder with a uniform surface coating is obtained by centrifugation, washing, and drying.

[0098] 4) The powder with uniform surface coating obtained in step 3) is calcined at 800° C. in an oxygen atmosphere for 2 h to form a high nickel single crystal positive electrode material with dual modification of Nb and Al.

[0099] (ii) Structural and morphological characterization (specific steps are the same as in Example 1).

[0100] (III) Preparation of interface-modified NCM electrode sheet (specific steps are the same as those in Example 1).

[0101] (IV) Assembling the battery (the specific steps are the same as those in Example 1).

[0102] (V) Battery testing (specific steps are the same as in Example 1).

[0103] Example 6

[0104] (I) Modification of positive electrode materials

[0105] 1) Dissolve 0.16 ml of niobium ethoxide and 0.19 g of aluminum nitrate nonahydrate in 10 ml of diethylene glycol, and stir at room temperature for 12 hours to form a precursor solution A;

[0106] 2) 10g high nickel single crystal positive electrode LiNi 0.8 Co 0.1 Mn 0.1 O2(NCM) particles (particle size 1-10 μm) were dispersed in 40 ml of acetone and dispersed evenly by ultrasonic stirring to form suspension B;

[0107] 3) The precursor solution A is slowly added dropwise to the suspension B by a peristaltic pump, and the mixture is stirred for 1 hour at room temperature. A powder with a uniform surface coating is obtained by centrifugation, washing, and drying.

[0108] 4) The powder with uniform surface coating obtained in step 3) is calcined at 750° C. in an oxygen atmosphere for 6 h to form a high nickel single crystal positive electrode material with dual modification of Nb and Al.

[0109] (ii) Structural and morphological characterization (specific steps are the same as in Example 1).

[0110] (III) Preparation of interface-modified NCM electrode sheet (specific steps are the same as those in Example 1).

[0111] (IV) Assembling the battery (the specific steps are the same as those in Example 1).

[0112] (V) Battery testing (specific steps are the same as in Example 1).

[0113] Example 7

[0114] (I) Modification of positive electrode materials

[0115] 1) Dissolve 0.16 ml of niobium ethoxide and 0.19 g of aluminum nitrate nonahydrate in 10 ml of diethylene glycol, and stir at room temperature for 12 hours to form a precursor solution A;

[0116] 2) 10g high nickel single crystal positive electrode LiNi 0.8 Co 0.1 Mn 0.1 O2(NCM) particles (particle size 1-10 μm) were dispersed in 40 ml of acetone and dispersed evenly by ultrasonic stirring to form suspension B;

[0117] 3) The precursor solution A is slowly added dropwise to the suspension B by a peristaltic pump, and the mixture is stirred for 1 hour at room temperature. A powder with a uniform surface coating is obtained by centrifugation, washing, and drying.

[0118] 4) The powder with uniform surface coating obtained in step 3) is calcined at 750° C. in an oxygen atmosphere for 1 h to form a high nickel single crystal positive electrode material with dual modification of Nb and Al.

[0119] (ii) Structural and morphological characterization (specific steps are the same as in Example 1).

[0120] (III) Preparation of interface-modified NCM electrode sheet (specific steps are the same as those in Example 1).

[0121] (IV) Assembling the battery (the specific steps are the same as those in Example 1).

[0122] (V) Battery testing (specific steps are the same as in Example 1).

[0123] Comparative Example 1

[0124] (I) Preparation of positive electrode materials

[0125] 1) 10g high nickel single crystal positive electrode LiNi 0.8 Co 0.1 Mn 0.1 O2(NCM) particles (particle size 1-10 μm) were dispersed in 40 ml of acetone and stirred at room temperature for 1 h, centrifuged, washed, and dried to obtain powder;

[0126] 2) The dried powder obtained in step 1) is calcined at 750° C. in an oxygen atmosphere for 2 h to obtain an unmodified high-nickel single crystal positive electrode material.

[0127] (ii) Structural and morphological characterization (specific steps are the same as in Example 1).

[0128] (III) Preparation of NCM electrode sheet (specific steps are the same as those in Example 1).

[0129] (IV) Assembling the battery (the specific steps are the same as those in Example 1).

[0130] (V) Battery testing (specific steps are the same as in Example 1).

[0131] Table 1

[0132]

[0133]

[0134] The data in the accompanying drawings and Table 1 of the specification show that by conveniently adjusting the appropriate Nb / Al ratio, coating thickness, and selecting the appropriate heat treatment temperature and time, the cycle stability of the high-nickel positive electrode can be maximized without losing its initial charge and discharge capacity. The reason may be that the introduction of an appropriate amount of Nb and Al double interface layers at the same time is conducive to stabilizing the interface structure of the layered positive electrode and promoting the transmission of lithium ions. The amount of metal salt introduced is too small to form a uniform and complete coating layer, and the introduction of excessive amounts will be detrimental to the transmission of lithium ions. The later heat treatment temperature is too high and the time is too long, which is not conducive to the stability of the crystal structure of the material itself. Accompanied by the generation of harmful impurities, it will cause a significant loss of capacity and is not conducive to maintaining the cycle stability of the material. Low heat treatment temperature and short treatment time are not conducive to the full conversion of the surface coating layer at the interface of the electrode material, and are not conducive to the transmission dynamics of lithium ions, thereby affecting its capacity and stability.

[0135] Figure 5The charge and discharge curves of the positive electrode material at a rate of 0.2C (in the range of 3-4.3V) after the conditions were optimized in Example 1 are shown. The high-nickel sample after interface modification shows similar charge and discharge curve characteristics to the original sample, and the discharge specific capacity of the modified sample can still reach 190.8mAh / g, indicating that appropriate modification will not cause the attenuation of the initial capacity. Figure 6 This is a comparison chart of the cycling performance of the modified sample in Example 1 and the unmodified sample at 1C rate. After 100 cycles, the modified sample showed a significantly improved capacity retention rate of up to 96.4%, which reflects that the Nb and Al interface co-modification strategy has obvious advantages in improving the cycling stability of the positive electrode material.

[0136] Comparative Example 2

[0137] (I) Preparation of positive electrode materials

[0138] 1) Dissolve 0.32 ml of niobium ethoxide in 10 ml of diethylene glycol, and stir at room temperature for 12 hours to form a precursor solution A;

[0139] 2) 10g high nickel single crystal positive electrode LiNi 0.8 Co 0.1 Mn 0.1 O2(NCM) particles (particle size 1-10 μm) were dispersed in 40 ml of acetone and dispersed evenly by ultrasonic stirring to form suspension B;

[0140] 3) The precursor solution A is slowly added dropwise to the suspension B by a peristaltic pump, and the mixture is stirred for 1 hour at room temperature. The treated powder is obtained by centrifugation, washing and drying.

[0141] 4) The dried powder obtained in step 3) is calcined at 750° C. in an oxygen atmosphere for 2 h to form a single Nb-modified high-nickel single crystal positive electrode material.

[0142] (ii) Structural and morphological characterization (specific steps are the same as in Example 1).

[0143] (III) Preparation of interface-modified NCM electrode sheet (specific steps are the same as those in Example 1).

[0144] (IV) Assembling the battery (the specific steps are the same as those in Example 1).

[0145] (V) Battery testing (specific steps are the same as in Example 1).

[0146] Comparative Example 3

[0147] (I) Preparation of positive electrode materials

[0148] 1) Dissolve 0.38 g of aluminum nitrate nonahydrate in 10 ml of diethylene glycol, and stir at room temperature for 12 h to form a precursor solution A;

[0149] 2) 10g high nickel single crystal positive electrode LiNi 0.8 Co 0.1 Mn 0.1 O2(NCM) particles (particle size 1-10 μm) were dispersed in 40 ml of acetone and dispersed evenly by ultrasonic stirring to form suspension B;

[0150] 3) The precursor solution A is slowly added dropwise to the suspension B by a peristaltic pump, and the mixture is stirred for 1 hour at room temperature. The treated powder is obtained by centrifugation, washing and drying.

[0151] 4) The dried powder obtained in step 3) is calcined at 750° C. in an oxygen atmosphere for 2 h to form a single Al-modified high-nickel single crystal positive electrode material.

[0152] (ii) Structural and morphological characterization (specific steps are the same as in Example 1).

[0153] (III) Preparation of interface-modified NCM electrode sheet (specific steps are the same as those in Example 1).

[0154] (IV) Assembling the battery (the specific steps are the same as those in Example 1).

[0155] (V) Battery testing (specific steps are the same as in Example 1).

[0156] Based on the advantages of the cycle stability of the above-mentioned Example 1 in the range of 3 to 4.3 V, its cycle stability under extreme conditions of high cut-off voltage of 4.5 V was further tested, and compared with Comparative Examples 2 and 3. Figure 7 To test the cycle curve at 1C rate in the test voltage range of 3-4.5V, the high nickel sample after Nb and Al co-modification showed excellent high-voltage stability. After 100 cycles, the capacity retention rate remained at 93%, which was much higher than Comparative Example 3 (91%), Comparative Example 2 (85%), and Comparative Example 1 (82%). This shows that the strategy of Nb and Al co-modification creates a more stable interface structure, which is completely different from the single interface modification. This has obvious advantages for improving the cycle stability of the positive electrode material at high cut-off voltage.

[0157] The above is a description of the exemplary embodiments of the present invention. However, the protection scope of the present application is not limited to the above embodiments. Any modification, equivalent substitution, improvement, etc. made by those skilled in the art within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for constructing a positive electrode material co-modified with niobium and aluminum, characterized in that: The construction method comprises the following steps: (1) mixing a soluble metal niobium salt, a metal aluminum salt and an alcohol solvent and reacting them to form a solution A; (2) adding the positive electrode active material to the anti-solvent and mixing to form a suspension B; (3) mixing the solution A obtained in step (1) with the suspension B obtained in step (2), and reacting them under stirring to obtain a powder with a uniform surface coating; (4) calcining the powder with uniform surface coating obtained in step (3) to obtain a positive electrode material co-modified with niobium and aluminum.

2. The construction method according to claim 1, characterized in that: In step (1), the alcohol solvent includes but is not limited to one or more of ethylene glycol, propylene glycol, tetraethylene glycol, diethylene glycol, triethylene glycol, tetraethylene glycol, hexaethylene glycol, octaethylene glycol, polyethylene glycol 200, polyethylene glycol 400, and polyethylene glycol 600. Preferably, in step (1), the soluble niobium salt is selected from at least one soluble metal niobium salt containing metal niobium element. Preferably, in step (1), the soluble aluminum salt is selected from at least one soluble metal aluminum salt containing metallic aluminum element. Preferably, in step (1), the concentration of the soluble niobium salt in solution A is 1×10 -4 ~1mol / L. Preferably, in step (1), the concentration of soluble aluminum salt in solution A is 1×10 -4 ~1mol / L. Preferably, in step (1), the reaction conditions for forming solution A include: the reaction temperature is room temperature to 50° C.; and the reaction time is 2 h to 72 h.

3. The construction method according to claim 1 or 2, characterized in that: In step (2), the positive electrode active material includes but is not limited to at least one of the positive electrode materials of lithium ion batteries, such as high nickel ternary nickel cobalt manganese oxide, lithium nickel oxide, lithium cobalt oxide, lithium manganese oxide, lithium-rich manganese-based materials, lithium nickel manganese oxide, lithium nickel cobalt oxide, lithium nickel cobalt aluminum oxide, lithium titanate, lithium iron phosphate, sodium ion battery positive electrode materials, and potassium ion battery positive electrode materials. Preferably, in step (2), the concentration of the positive electrode active material is 1×10 -2 ~20mol / L. Preferably, in step (2), the anti-solvent includes but is not limited to at least one of methanol, ethanol, propanol, acetone, butanone, chloroform, dichloromethane, furfural, acetonitrile, dioxane, ethyl acetate, acetic acid, formic acid, acetic anhydride, acetylacetone, acetaldehyde, and tetrahydrofuran.

4. The construction method according to any one of claims 1 to 3, characterized in that: In step (3), the method of mixing solution A with suspension B includes: directly pouring the solution, slowly dripping, and controlling the dripping rate by a peristaltic pump to drip into solution B; or, directly pouring solution B, slowly dripping, and controlling the dripping rate by a peristaltic pump to drip into solution A. Preferably, the dripping rate controlled by the peristaltic pump is 0.1 ml / min-30 ml / min. Preferably, in step (3), the stirring temperature is from room temperature to 50°C. Preferably, in step (3), the stirring speed is between 100 r / min and 1000 r / min. Preferably, in step (3), the coating layer thickness of the powder uniformly coated on the surface is between 1 and 200 nm.

5. The construction method according to any one of claims 1 to 4, characterized in that: In step (4), the calcination atmosphere is at least one of oxygen, air, nitrogen and argon. Preferably, in step (4), the calcination temperature is 200 to 900°C; Preferably, in step (4), the calcination time is 1 to 10 hours.

6. The construction method according to any one of claims 1 to 5, characterized in that: In step (4), the shell structure of the positive electrode material co-modified with Nb and Al is a composite interface layer containing niobium and aluminum.

7. A positive electrode material co-modified with Nb and Al, characterized in that: The positive electrode material is obtained by the construction method according to any one of claims 1 to 6.

8. The positive electrode material according to claim 7, characterized in that The positive electrode material co-modified with Nb and Al is a particle with a core-shell structure.

9. The positive electrode material according to claim 7 or 8, characterized in that: The Nb and Al co-modified positive electrode material comprises a shell structure and a positive electrode active substance, wherein the shell structure is modified on the surface of the positive electrode active substance; and the shell structure comprises at least Nb and Al elements. Preferably, the shell structure partially or completely covers the surface of the positive electrode active material. Furthermore, the shell structure is continuously and evenly distributed on the surface of the positive electrode active material. Preferably, the shell structure has a thickness of 0 nm to 200 nm.

10. Use of the Nb and Al co-modified positive electrode material according to any one of claims 7 to 9 in energy storage batteries.

Citation Information

Patent Citations

  • Method for coating lithium-ion battery cathode material with aluminum oxide

    CN108336348A

  • High-nickel positive electrode material with uniform coating layer and preparation method thereof

    CN109950498A

  • Preparation method of niobium-aluminum co-doped lithium-ion battery cathode material

    CN110190276A

  • Alumina complex powder and polycrystal alumina sintered material and the fabrication method thereof

    KR1020120064520A

  • Process for the purification of lithium salts

    US20220402773A1

Cited By

  • Niobium and aluminum co-doped high-nickel ternary positive electrode material as well as preparation method and application thereof

    CN121307014A